PolyMeCo: uma ferramenta para análise e comparação de malhas poligonais - Silva, Samuel (2008)
Polygonal meshes are used in several application areas to model different objects and structures. Depending on the application, such models have sometimes to be processedto, for instance, reduce their complexity (mesh simplification). Such processing introduces error, whose evaluation is of paramount importance. Although some mesh analysis and comparison tools are described in the literature, little attention has been given to the way mesh features and mesh comparison results can be visualized. PolyMeCo, a tool for polygonal mesh analysis and comparison, was designed and developed to enhance the way users perform mesh analysis and comparison, by providing an integrated environment where various mesh quality measures and several visualization options are available.